PatchMatch-Based Neighborhood Consensus for Semantic Correspondence - Lee, Jae Yong; DeGol, Joseph; Fragoso, Victor; Sinha, Sudipta (Computer Vision and Pattern Recognition (CVPR 2021), 2021)
We address estimating dense correspondences between two images depicting different but semantically related scenes. End-to-end trainable deep neural networks incorporating neighborhood consensus cues are currently the best methods for this task. However, these architectures require exhaustive matching and 4D convolutions over matching costs for all pairs of feature map pixels. This makes them computationally expensive. We present a more efficient neighborhood consensus approach based on PatchMatch. For higher accuracy, we propose to use a learned local 4D scoring function for evaluating candidates during the PatchMatch iterations. We have devised an approach to jointly train the scoring function and the feature extraction modules by embedding them into a proxy model which is end-to-end differentiable. The modules are trained in a supervised setting using a cross-entropy loss to directly incorporate sparse keypoint supervision. Our evaluation on PF-PASCAL and SPAIR-71K shows that our method significantly outperforms the state-of-the-art on both datasets while also being faster and using less memory.